Guided Reading for Second Language Learning in Bahrain: Is it Worth it - Ali, Afrah Hassan (2010)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) by Afrah Hassan Ali Entitled, "Guided Reading for Second Language Learning in Bahrain: Is it Worth it," May 2010. Available are both Hard and Soft Copies of the Thesis.